2004
DOI: 10.1016/j.biosystems.2004.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal evolution: analysis of regulatory genes in a first-evolved nervous system, the hydra nervous system

Abstract: Cnidarians represent the first animal phylum with an organized nervous system and a complex active behavior. The hydra nervous system is formed of sensory-motoneurons, ganglia neurons and mechanoreceptor cells named nematocytes, which all differentiate from a common stem cell. The neurons are organized as a nerve net and a subset of neurons participate in a more complex structure, the nerve ring that was identified in most cnidarian species at the base of the tentacles. In order to better understand the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 74 publications
1
35
0
1
Order By: Relevance
“…Immunohistochemical studies have shown a great deal of molecular complexity in neuropeptide expression in Hydra (66,67), and gene expression studies with an increasingly broad range of molecular markers with potential roles in neural patterning have highlighted distinct domains of the N. vectensis body plan. NvNetrin is expressed in the same longitudinal stripe of body wall where several Hox genes are expressed.…”
Section: Discussion Evolutionary Predecessor Of the D-v Axis?mentioning
confidence: 99%
“…Immunohistochemical studies have shown a great deal of molecular complexity in neuropeptide expression in Hydra (66,67), and gene expression studies with an increasingly broad range of molecular markers with potential roles in neural patterning have highlighted distinct domains of the N. vectensis body plan. NvNetrin is expressed in the same longitudinal stripe of body wall where several Hox genes are expressed.…”
Section: Discussion Evolutionary Predecessor Of the D-v Axis?mentioning
confidence: 99%
“…Notably, signalling through the RXR receptor has been examined in several species of cnidarian; exogenous application of retinoic acid has been shown to play a role in promoting metamorphosis in the jellyfish Aurelia aurita [94] and regulating the development of the eyes in the box jelly Tripedalia cystophora [95]. Further, the COUP-TF transcription factor (NR2 family) is an important regulator of neurogenesis in hydrozoans [96,97]. While Reitzel & Tarrant [87] demonstrated differential expression of NRs through developmental time in N. vectensis, without spatial analysis of gene expression it is difficult to hypothesize what role these diverse receptors may play in embryogenesis of the sea anemone.…”
Section: (B) Canonical Wnt Signallingmentioning
confidence: 99%
“…Together with the ctenophores, the Cnidaria form the Coelenterata, the sister group of Bilateria (52). It is assumed that transduction of chemical and mechanical stimuli in nematocytes are hallmarks of primitive nerve cells and that nematocytes are thus representative of ancestral sensory cells that preceded the differentiation of neuronal cell types in animal evolution (53). The unequivocal expression of Ngbs in nematocytes of the jellyfish C. hemisphaerica appears to be a robust indication of the essential role of these proteins in early evolution of the nervous system.…”
Section: In the Cnidarian C Hemisphaerica Two Globins (Chengb1 And mentioning
confidence: 99%